Conductive Tracks in Carbon Implanted Titania Nanotubes: Atomic‐Scale Insights from Experimentally Based Ab Initio Molecular Dynamics Modeling. Issue 6 (11th March 2022) - Holm, Alexander; Kupferer, Astrid; Mändl, Stephan; Lotnyk, Andriy; Mayr, Stefan G.
Abstract: Ion implantation of titania nanotubes is a highly versatile approach for tailoring structural and electrical properties. While recently self‐organized nanoscale compositional patterning has been reported, the atomistic foundations and impact on electronic structure are not established at this point. To study these aspects, ab initio molecular dynamic simulations based on atomic compositions in C implanted titania nanotubes according to elastic recoil detection analysis are employed. Consistent with experimental data, carbon accumulates in chainlike precipitates, which are favorable for enhancing conductivity, as revealed by density‐functional theory electronic ground states calculations are demonstrated. Abstract : Ab initio molecular dynamics simulations based on elastic recoil detection analysis unveil nanoscale precipitation in C implanted amorphous titania nanotubes. In discussing electron transport mechanisms, emerging nanostructures, and short‐range order, this atomic picture extends the authors' previously derived continuum picture to explain compositional pattering observed in irradiated nanotubes.